Tribological study of castor oil with surface-modified CuO nanoparticles in boundary lubrication - Gupta R.N.; Harsha A.P. (My University, 2025)
Purpose: The present work aims to formulate nanolubricants and improve antiwear, antifriction and extreme pressure (EP) performances of castor oil (CO) with surface-modified CuO nanoparticles as an additive in the boundary lubrication regime. Design/methodology/approach: In this study, CuO nanoparticles are modified with a surfactant sodium dodecyl sulfate (SDS) by means of a chemical method. These modified nanoparticles with varying concentrations of 0.1, 0.25, 0.5 and 1.0%w/v were used to formulate the nanolubricants. The tribological properties of non-formulated and formulated CO were examined using a four-ball tester. The tribological test results were compared with paraffin oil (PO) for similar compositions. Findings: The nanoparticle concentrations in base oils were optimized by wear scar diameter (WSD) and load carrying capacity during antiwear and EP tests, respectively. In the antiwear test, the maximum reductions in WSD were 28.3 and 22.2 per cent; however, the coefficient of friction was reduced by 34.6 and 17.3 per cent at optimum nanoparticle concentrations in CO and PO, respectively. A significant improvement in the weld load was observed for both nanolubricants. Originality/value: This work indicates that nanoparticle-based CO in industrial applications provides on par or better results than mineral oil. Also, it has a negligible hazardous impact on our eco-system. © 2018, Emerald Publishing Limited.